2005
DOI: 10.1002/smi.1065
|View full text |Cite
|
Sign up to set email alerts
|

Post‐traumatic reactions among rescue personnel 96 hours after the Hilton Hotel bombing in Sinai: The effect of previous exposure

Abstract: This paper considers the immediate post‐traumatic reactions of rescue personnel who were exposed to the Hilton Hotel bombing in Sinai. The entire rescue personnel (n = 26) were assessed and separated into two groups on the basis of previous exposure to the same type of trauma. The results suggest that among rescue personnel, those with previous exposure had a lower level of post‐traumatic symptoms than those who were being exposed for the first time. This supports the hypothesis that previous exposure to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
1
18
1
Order By: Relevance
“…In contrast, the cumulative effect of dissimilar traumatic event exposure will result in more posttraumatic stress symptoms (Dougall et al, 2000;McDermu et al, 2000). The findings of a recent study by Ben-Ezra, Essar, and Saar (2005) support the separation of similar from dissimilar traumatic event exposure. The researchers asked study participants to fill out a three-part questionnaire about The study compared rescue personnel with previous exposure to similar traumatic experiences and those experiencing their first exposure.…”
Section: Applying a Cumulative Stress Model To Predict Individual Difsupporting
confidence: 79%
“…In contrast, the cumulative effect of dissimilar traumatic event exposure will result in more posttraumatic stress symptoms (Dougall et al, 2000;McDermu et al, 2000). The findings of a recent study by Ben-Ezra, Essar, and Saar (2005) support the separation of similar from dissimilar traumatic event exposure. The researchers asked study participants to fill out a three-part questionnaire about The study compared rescue personnel with previous exposure to similar traumatic experiences and those experiencing their first exposure.…”
Section: Applying a Cumulative Stress Model To Predict Individual Difsupporting
confidence: 79%
“…[2][3] A substantial number of studies have checked for post-traumatic stress among rescue personnel. [1][2][3][4][5][6] Little or no studies have examined acute stress symptoms within the first day after exposure to a traumatic event. The effect of exposure to dead bodies on rescue personnel only has been addressed by few studies.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of exposure to dead bodies on rescue personnel only has been addressed by few studies. 1,[5][6][7] Based on the existing literature, it was predicted that among rescue per sonnel, the immediate acute stress symptoms would be higher among those who had had previous exposure to dead bodies. This hypothesis is based on studies that have considered exposure to dead bodies as an extremely stressful event for rescue personnel and resulted in a long-term psychological impact.…”
Section: Introductionmentioning
confidence: 99%
“…The DES is used to assess retrospective reports of dissociation during a traumatic experience. The IES-R and DES were used in earlier studies that explored the immediate reactions to psychological trauma and were found sensitive, valid, and reliable (Ben-Ezra et al, 2005;Ben-Ezra, Essar, & Saar, 2006).…”
Section: Instrumentsmentioning
confidence: 99%
“…However, a small number of studies have included a measure of the level of dissociation within the first days after traumatic events (Ben-Ezra, Essar, & Saar, 2005;Birmes et al, 2003). The empirical evidence for the relationship between dissociation and posttraumatic symptoms within the first days after exposure to traumatic events is scarce (Bryant, 2007;Bryant & Harvey, 1997).…”
mentioning
confidence: 99%